LOBBYING AS STRATEGIC COMMUNICATION IN PRACTICE - THE CROWN OF THE SEPARATIST MOVEMENT ON KOSOVO AND METOHIJA (Heritage, 2022)
Strategic communication is one of the expressions of the soft power and represents an instrument in the political and security achievement of national interests. One of the strategic communication forms is lobbying. Potential lobbying of foreign policy is significant, as it could bе realized through direct military intervention for support of interest group goals. The paper presents gained results of interest representation of Albanian interest groups regarding U.S. foreign policy as support of the achievement of the separatists' goal in the form of the Republic of Kosovo. Using content analysis and conclusions synthesis, the paper presents results that indicate effective and productive effects of applied interest representation strategy. It is a suggested that base of common interest should focus on political, economic and security interests, and institutional preconditions for effective lobbying of U.S. institutions. Conclusions indicate that organized and strategically planed lobbying approach to U.S. institutions can bring very good results.
Keywords: strategic communication, ethnic interest groups, lobbying, U.S. foreign policy, Kosovo